Poverty and water (London Zed Books, 2008)
Rarely has such a contentious and complex issue emerged in twenty-first century development as that of water. In this book, co-editors David Hemson, Kassin Kulindwa, Haakon Lein, and Adolfo Mascarenhas use a global spread of case studies to illustrate that water is not simply an issue of physical scarcity, but rather a complex and politically-driven issue with profound future implications, both in the developing world and outside it. The book argues that for the international community to achieve the Millennium Development Goals, governments must step in to protect the rights of the poor. Here, the links between poverty and access to clean water are explored with an eye to political reform that can end the exploitative policies of big business and help to shape a more equitable world for all.
Includes bibliographical references and index.
Keywords: Water-supply--Economic aspects--Developing countries--Case studies